Supporting play in early childhood : environment, curriculum, assessment - Dorothy Justus Sluss (Stamford, Connecticut : Cengage Learning Asia Pte Ltd, 2015)
Aimed at teachers and future teachers of children from birth through age eight, this book examines the positive effects of play on children's social/emotional, cognitive, and physical development. It helps them learn how to assess a child's learning through play, making play a practicable teaching mechanism
Part 1. Theories and Foundation of Play -- Part 2. Play in Early Education -- Part 3. Play in School Setting -- Part 4. Beyond the Classroom .
Includes index.
Keywords: EARLY CHILDHOOD EDUCATION